Efficient 2-D leaky-wave antenna configurations based on graphene metasurfaces. Issue 6 (9th May 2017) - Fuscaldo, Walter; Burghignoli, Paolo; Baccarelli, Paolo; Galli, Alessandro
Abstract : Different configurations of leaky-wave antennas (LWAs) based on graphene metasurfaces are studied. The electronic properties of a graphene metasurface in the low THz range are investigated in details in order to discuss the reconfigurability features of the presented structures. Simple exact formulas for evaluating the ohmic losses related to the surface plasmon polariton (SPP) propagation along a suspended graphene sheet, and the relevant figures of merit of SPP propagating over a generic metasurface are given. Such formulas allow us to explain the low efficiency of reconfigurable antennas based on SPPs along graphene metasurfaces. Then, the radiative performance and relevant losses of graphene Fabry–Perot cavity antennas (FPCAs) based on non-plasmonic leaky waves (LWs) are investigated and compared with previous solutions based on SPPs. In particular, a single-layer structure, i.e. a grounded dielectric slab covered with a graphene metasurface, and a multilayered structure, i.e. a substrate–superstrate antenna in which the graphene metasurface is embedded at a suitable position within the substrate, are considered in detail. The results show that the proposed LW solutions in graphene FPCAs allow for considerably reducing the ohmic losses, thus significantly improving the efficiency of the proposed radiators.